Spain in British Romanticism 1800-1840 (Nineteenth-Century Major Lives and Letters, 2018)
This collection of thirteen specially commissioned essays by international scholars takes a fresh look at the profound impact of the Peninsular War on Romantic British literature and culture. The expertly authored chapters explore the valorization of Spain by nineteenth-century poets such as Lord Byron, William Wordsworth, Robert Southey, S.T. Coleridge, the Shelleys, and Felicia Hemans in contrast to the Enlightenment-era view of Spain as a backwards nation in decline. Topics discussed include the vision of Spain in Gothic fiction, Spanish experiences of exile as exemplified by the conflict between Valentin de Llanos and Joseph Blanco White, and British women writers' approach to peninsular fiction. Spain in British Romanticism: 1800-1840 is essential reading for scholars and enthusiasts of Romantic literature and Spanish history. .